2013
DOI: 10.1155/2013/748932
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Integrative Inpatient Treatment Based on DRG Data: The Example of Anthroposophic Medicine

Abstract: Background. Much work has been done to evaluate the outcome of integrative inpatient treatment but scarcely the costs. This paper evaluates the costs for inpatient treatment in three anthroposophic hospitals (AHs). Material and Methods. Cost and performance data from a total of 23,180 cases were analyzed and compared to national reference data. Subgroup analysis was performed between the cases with and without anthroposophic medical complex (AMC) treatment. Results. Costs and length of stay in the cases withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
1
7
1
Order By: Relevance
“…On the contrary, hospitals expenditures per day of each hospitalization were higher in the V group compared to the C group. is can be explained by the application of several Anthroposophic add-on complementary therapies (beyond add-on VA therapy) [29,30]. However, compared to earlier studies on pancreatic carcinoma, our data indicate less visits and shorter hospitalization time of the total observed mPC cohort in our study, reflecting current real-life treatment of pancreatic cancer patients as they lie shorter and most of the preparations are increasingly performed in an ambulant setting [31].…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…On the contrary, hospitals expenditures per day of each hospitalization were higher in the V group compared to the C group. is can be explained by the application of several Anthroposophic add-on complementary therapies (beyond add-on VA therapy) [29,30]. However, compared to earlier studies on pancreatic carcinoma, our data indicate less visits and shorter hospitalization time of the total observed mPC cohort in our study, reflecting current real-life treatment of pancreatic cancer patients as they lie shorter and most of the preparations are increasingly performed in an ambulant setting [31].…”
Section: Discussioncontrasting
confidence: 41%
“…Rather, a combination of the slightly higher number of hospital stays due to longer survival, as shown here for the V treatment, would serve as an explanation. It has been reported that the coincidence of complementary treatment with increased care durations does not have to be necessarily correlated to a more severe disease status of patients [29]. Given a simultaneous better effectiveness in the present study, combinational therapy with add-on VA has been shown to be noninferior to standard of care alone in terms of cost-effectiveness revealing hospital's savings for this treatment compared to the control.…”
Section: Discussionmentioning
confidence: 47%
“…Personalized add-on therapies are listed on a structured weekly plan, which is handed out to the patient. Analogous to complex treatments in palliative care (national OPS code 8-982 (German surgical operation and procedure classification)), chronic pain (OPS code 8-918), and natural medicine (OPS code 8-975.2) where specific minimal criteria must be obeyed, an additional payment for integrative anthroposophical complex treatments (national OPS code 8-975.3) is granted by health insurance companies if at least 30 therapeutic units are documented for the patient within 1 hospital stay [27]. In a weekly inter-professional patient conference, the therapeutic interventions of each patient are discussed among physicians, nurses, and therapists.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this data, a predetermined reimbursement rate per case is calculated [19]. For long-stay outlier cases, however, hospitals receive additional reimbursement for every day that the patient stays above the upper length of the stay threshold [20].…”
Section: Discussionmentioning
confidence: 99%